Comparison of two isolation methods of tobacco-derived extracellular vesicles, their characterization and uptake by plant and rat cells - Kocholata, Michaela; Prusova, Michaela; Auer Malinska, Hana; Maly, Jan; Janouskova, Olga (Scientific reports, 2022)
Plant extracellular vesicles (pEVs) derived from numerous edible sources gain a lot of attention in recent years, mainly due to the potential to efficiently carry bioactive molecules into mammalian cells. In the present study, we focus on isolation of PDNVs (plant-derived nanovesicles) and pEVs from callus culture and from BY-2 culture of Nicotiana tabacum (tobacco). Tobacco was selected as a source of plant vesicles, as it is commonly used by human, moreover it is a model organism with established techniques for cultivation of explant cultures in vitro. Explant cultures are suitable for the isolation of pEVs in large quantities, due to their fast growth in sterile conditions. As the efficiency of isolation methods varies, we were comparing two methods of isolation. We evaluated biophysical and biochemical properties of plant vesicles, as well as differences between isolates. We encountered difficulties in the form of vesicles aggregation, which is often described in publications focused on mammalian nanovesicles. In an effort to prevent vesicle aggregation, we used trehalose in different stages of isolation. We show tobacco-derived vesicles successfully enter tobacco and mesenchymal cell lines. We observed that tobacco-nanovesicles isolated by different methods incorporated fluorescent dye with different efficiency. The results of our study show tobacco-derived vesicles isolated by various isolation methods are able to enter plant, as well as mammalian cells.
Keywords: extracelulární vezikuly; Nicotiana; savci; Plants; Rats; Mesenchymal Stem Cells; Humans; zvířata; Extracellular Vesicles; Mammals; mezenchymální kmenové buňky; Animals; krysa rodu Rattus; Biological Transport; tabák; lidé; biologický transport; rostliny